Names versus faces: examining spokesperson-based congruency effects in advertising. Issue 1 (9th February 2015) - Ilicic, Jasmina; Baxter, Stacey; Kulczynski, Alicia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to compare the influence of spokesperson appearance (visual congruence) and the sounds contained in a spokesperson's name (verbal congruence) on consumer perceptions of spokesperson–product fit. Design/methodology/approach – Two experiments were conducted. Experiment 1 ensured that verbal congruence impacted perceptions of spokesperson–product fit. Experiment 2 compared the effect of verbal congruence versus traditional match-up (visual congruence) on perceptions of spokesperson–product fit. The mediating role of spokesperson–product fit on attitude towards the advertisement and the moderating role of need for cognition (NFC) was also tested. Findings – Findings indicate that verbal congruence influences consumer perceptions of fit, regardless of visual congruence. Perceptions of spokesperson–product fit also act as mediators between visual and verbal congruence and attitude towards the advertisement. However, verbal congruence did not influence consumer perceptions of spokesperson–product fit when the NFC was low. Research limitations/implications – This research has implications for advertisers and brand managers considering the creation of a name for a non-celebrity spokesperson or the development of a brand/spokes-character. However, this research is limited, as it examines only male names. Originality/value – This research shows that perceptions of spokesperson and product fit are not only influenced by spokesperson appearance (visual congruence) but also by spokesperson name (verbal congruence). This research also identifies limitations of the applicability of phonetic symbolism theory by identifying a condition under which phonetic symbolism (verbal congruence) exerts no effects on perceptions of spokesperson–product fit.